2009
DOI: 10.1159/000210265
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Motor Function Abnormalities in Gastroesophageal Reflux Disease and Barrett’s Esophagus

Abstract: Barrett’s esophagus has traditionally been regarded as the most severe end of the spectrum of gastroesophageal reflux disease and is of great clinical importance in view of the association with esophageal adenocarcinoma. Studies have documented high levels of esophageal acid exposure in Barrett’s esophagus. Various pathogenetic mechanisms underlie this phenomenon. These include abnormalities in esophageal peristalsis, defective lower esophageal sphincter pressures, gastric dysmotility and bile reflux. Whilst t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 212 publications
(151 reference statements)
1
33
0
2
Order By: Relevance
“…This fact coincides with the findings of Meneguetti et al (25) and Jorge et al (21) who also concluded that as the amount of mucosal damage increased from group without esophagitis to Barrett's esophagus, both esophageal motility and acid clearance worsened, suggesting that esophageal mucosal damage may contribute to esophageal dysmotility and worsening reflux (9) and that there is a direct relationship between the impairment of motor function and severity of esophageal reflux esophagitis (4,30) .…”
Section: Discussionsupporting
confidence: 87%
“…This fact coincides with the findings of Meneguetti et al (25) and Jorge et al (21) who also concluded that as the amount of mucosal damage increased from group without esophagitis to Barrett's esophagus, both esophageal motility and acid clearance worsened, suggesting that esophageal mucosal damage may contribute to esophageal dysmotility and worsening reflux (9) and that there is a direct relationship between the impairment of motor function and severity of esophageal reflux esophagitis (4,30) .…”
Section: Discussionsupporting
confidence: 87%
“…48 The aetiology of Barrett's mucosa, which represents the severest end of the reflux spectrum, is in turn a consequence of altered gastrointestinal anatomy and physiological mechanisms 49 the most significant of which are the alteration in intestinal motility 50 Gallbladder volume decreased gradually after the standard meal in all groups. The gallbladder volume decrease was slower in the Barrett's group and the cancer group and continued up to 60 min with no recovery toxicity of the resultant refluxate.…”
Section: Discussionmentioning
confidence: 99%
“…Since then this hypothesis has been widely accepted and recently most authors have agreed that the combined acidic and biliary reflux is one of the most important pathophysiological factors of the disease [23,31,32]. In contrast, so far only small series of patients have been examined to test this hypothesis [11,26,33].…”
Section: Discussionmentioning
confidence: 99%